The years de Virginia Woolf: um romance da vida doméstica - Moura, Brena Suelen Siqueira (Revista Ártemis, 2022)
Virginia Woolf wrote in her diary in 1931 that she intended to write a book on women's sex lives, which would be a sequel to A Room of Own's One (1929). The Years (1937), Virginia Woolf's penultimate novel, explores the political, social, and economic changes of an English family over a period of 50 years. The year after the publication of The Years, Virginia Woolf explained the reasons why the educated men’s daughters did not have an important influence to prevent war in her essay Three Guineas. In The Years, it seems that these reasons are represented in the women's life trajectory of the Pargiter family. This article will investigate how Virginia Woolf's penultimate novel shows the society of her time since one of the female characters confesses not feeling the effects of the First World War. The Years’ narrative focuses on the everyday life of the characters of a privileged social class, inside their homes, amid their family chores and social gatherings. Perhaps it is possible to infer that the cause of Eleanor’s passivity would be because she was restricted to a private and domestic world. In this sense, this article proposes to read, through the Pargiter women’s biographies, the patriarchal society in which they were submerged. As a result, The Years writes the unwritten history of women from a family perspective, as the years pass in this novel and these historical, social, and political changes can be read from a private sphere.